Associations of CAG repeat polymorphism in the androgen receptor gene with steroid hormone levels and anthropometrics among men: the role of the ethnic factor - L. V. Osadchuk; G. V. Vasiliev; A. V. Osadchuk (Вавиловский журнал генетики и селекции)
Androgens are required for stimulation and maintenance of skeletal growth and bone homeostasis. Physiological functions of androgens are mediated through the androgen receptor (AR). The androgen receptor gene AR has a polymorphic trinucleotide CAG repeat and the length of AR CAG repeats determining the sensitivity of bone tissue to androgens is associated with skeleton formation and body proportions. This study aimed to investigate the relationship between AR CAG repeat polymorphism, circulating sex steroid hormones and the anthropometrics in males of different ethnic origins. Male volunteers of three ethnic groups (Slavs, Buryats, Yakuts) from urban Russian populations were recruited in a populationbased study (n = 1078). Anthropometric indicators (height, arm span, leg length, the length of 2 and 4 digits of both hands) were measured and the following anthropometric indices were calculated: the ratio of height to leg length, the ratio of arm span to height, the ratio of lengths of second to fourth digit of the hand. Serum testosterone and estradiol were determined by enzyme immunoassay. Genotyping of the AR CAG repeats was performed using fragment analysis and capillary electrophoresis. Ethnic differences in all anthropometric and hormonal indicators have been established, with higher anthropometric indicators in Slavs than Buryats, and in most cases higher than in Yakuts. The testosterone level was higher among Slavs compared to Buryats, but did not differ from Yakuts; the estradiol level was lower among Slavs compared to Buryats, who did not differ from Yakuts. Buryats and Yakuts had a higher number of CAG repeats than Slavs (medians: Slavs, 23; Buryats, 24; Yakuts, 25). Positive correlations were found between the length of AR CAG repeats and estradiol levels in Buryats and testosterone levels in Yakuts, while longer CAG repeats were accompanied by higher estradiol levels in Buryats and testosterone levels in Slavs and Yakuts. Ethnic-specific correlations have been established between the steroid hormone levels and some anthropometric indicators in all ethnic groups. Available data suggest that the ethnic-specific associations of AR CAG repeats with anthropometrics can be mediated by sex steroid hormones as important regulators of skeletal growth and bone homeostasis.